The Bhagavad Gita and Beyond: Synchronic Strategy for Sanskrit Narrative Literature - Balkaran, Raj (Religions of South Asia, 2021)
Paying particular attention to narrative frames, this paper explores five avenues of hermeneutic import availed by the interlocking structure of such texts: inception import, association import, exposition import, framing import and impetus import. It demonstrates the utility of this methodology by applying it to shed new light on the Bhagavad Gita’s place within the Mahabharata.